Management of severe recurrent focal segmental glomerulosclerosis through circulating soluble urokinase receptor modification - Morath, Christian; Wei, Changli; Macher-Göppinger, Stephan; Schwenger, Vedat; Zeier, Martin; Reiser, Jochen (American journal of therapeutics, 2013)
Circulating soluble urokinase receptor (suPAR) was recently identified as one of the causes responsible for native and recurrent focal segmental glomerulosclerosis (FSGS) through overactivation of podocyte β3 integrin. Here, we discuss the management of a patient with very high suPAR serum levels and FSGS recurrence. The suPAR reduction using plasmapheresis and immunoadsorption allowed for lowering of suPAR and reduced podocyte β3 integrin activation and proteinuria. The patient is successfully weaned to bimonthly suPAR removal treatments with improved renal parameters. In summary, we provide an approach for the successful management of severe recurrent FSGS using available therapies with biomarker guidance.
Gesehen am 07.06.2021